Ignition and Puffing Characteristics of Kerosene Droplets with Addition of Boron Particles and Water/Ethanol Under Sub-Atmospheric Pressure - Jie Huang; Hongkun Lv; Jing Nie; Liwei Ding; Xinrui Xiong; Kang Zhang; Jiaying Chen; Zhenya Lai; Zhihua Wang (Energies)
To address the problems of the reduced evaporation rate and increased ignition time of kerosene droplets at sub-atmospheric pressures and high temperatures, boron and ethanol/water were selected as additives to be blended with RP-3 kerosene, respectively. The effects of different types of blended fuels on the evaporation, micro-explosion, and spontaneous ignition characteristics of RP-3 kerosene droplets were tested and compared using an independently designed, high-temperature, controlled-pressure experimental droplet system. A low-pressure environment (0.4 bar) promoted the high-intensity micro-explosion of RP-3/B and RP-3/water/ethanol droplets while reducing the number of puffing events. A comparative study of RP-3/B and RP-3/ethanol/water found that ethanol/water blended fuels had a higher micro-explosion intensity (1000–10,000 vs. 0.2–15 mm/s) and shorter droplet lifetimes and self-ignition times at low pressure. The 30%water fuel (30 vol.%water in water/ethanol sub-droplet) had the shortest ignition/breakup time, with an ignition time of 0.5715 s at 0.8 bar, 26.92% shorter than RP-3’s 0.782 s. This 30%water fuel mixture can increase the release rate of combustible vapors prior to ignition by inducing puffing and micro-explosions at high temperatures.